Proximity Coupled Antenna With Star Geometry Pattern AMC Ground Plane - Maisarah, Abu; Maizatun, Muhamad; Hasnizom, Hassan; Zahriladha, Zakaria; Siti Adlina, Md Ali (Asian Research Publishing Network (ARPN), 2016)
In this paper, a conventional proximity coupled microstrip antenna operating at 2.45 GHz is firstly designed as a reference antenna. Then, the proximity coupled microstrip antenna is incorporated with a star geometry pattern artificial magnetic conductor (AMC) as the ground plane. Performance comparison is analyzed between the conventional antenna and the antenna with the AMC ground plane. The proximity antenna with star geometry pattern AMC ground plane successfully enhances the efficiency and gain by 8 % and 3 % as compared to the conventional antenna. In addition, the size of the proximity antenna with star geometry pattern AMC ground plane is reduced by 13 % as compared to conventional antenna. It shows that AMC as a ground plane to the antenna are able to reduce the size, enhance the gain and efficiency of the antenna.